Pieces of Sound : German Experimental Radio - Gilfillan, Daniel (Book collections on Project MUSE., 2009)
Since the rise of film and television, radio has continued to evolve and any understanding of the development of radio depends on closely examining the artistic ventures that preceded commercial acceptance. Daniel Gilfillan offers a cultural history that explores these aspects of the medium by focusing on German radio broadcasting, providing a context that sees beyond programming to consider regulations, cultural politics, and social standardization.